A chronological review of circularly polarized dielectric resonator antenna: Design and developments. Issue 5 (18th February 2021) - Meher, Priya Ranjan; Behera, Bikash Ranjan; Mishra, Sanjeev Kumar; Althuwayb, Ayman Abdulhadi
Abstract: This article presents a chronological overview of circularly polarized dielectric resonator antennas (CPDRAs). This article provides a comprehensive review about innovation and rapid developments of CPDRAs over the last three and half decades since 1986s. The objective of this article is to highlight the basic concept of CP mechanism in DRA and state‐of‐the‐art developments of CPDRAs in terms of single and multi‐point feed for unmodified and modified DR geometries considering different types of excitation mechanism such as microstrip line, coaxial probe, and aperture coupled feed. To give insights into circular polarization, Authors proposed a compact modified CPDRA. It offers simulated bandwidth of 47.5% (2.34‐3.80 GHz), measured impedance bandwidth of 50.8% (2.26‐3.78), and simulated axial bandwidth of 13% (3.29‐3.75 GHz) respectively. Other antenna parameters such as peak realized gain and radiation efficiency are 7.7 dBi and 98% within operating frequency bands, respectively. The proposed outcomes confirm that the proposed CPDRA can be used as a suitable candidate for wireless body area network applications.